Structural performance evaluation of cross dapped connection for vertical wall-to-wall connection of precast wall panel - Amril Hadri Jamaludin,; Noorsuhada Md Nor,; Amir Khomeiny Ruslan,; Soffian Noor Mat Saliah,; Nurul Ashikin Ahmad,; Ahmad Syauqi Md Hassan,; Mohd Azrizal Fauzi,; Nor Azian Aziz, (Penerbit Universiti Kebangsaan Malaysia, 2024)
In the context of Industrialised Building Systems (IBS), precast concrete buildings are composed of multiple structural members that are interconnected through different techniques. The adoption of precast concrete wall panels has gained significant traction in contemporary construction methodologies. Nevertheless, the utilization of dapped connections specifically designed for non-load bearing applications in precast walls incorporating recycled concrete aggregate (RCA) remains largely unexplored and limited in practice. This research proposes a new wall-to-wall connection for precast wall panels to enhance the constructability of IBS for non-load bearing walls. The novel Cross Dapped (CD) design enables horizontal panel installation in confined areas with existing structural frames, while ensuring the connection’s strength as a non-load bearing wall to prevent failure. Uniformly distributed loads are applied until sample failure, recording compressive load patterns, deflection, stress-strain patterns, and crack patterns on the wall surface. The CD connection demonstrates applicability for precast wall-to- wall connections, improving IBS constructability with its innovative design and locking system. Overall, this research explores and proposes an efficient and structurally sound wall-to-wall connection design for precast wall panels of non-load bearing system, facilitating the adoption of IBS methods, and improving the overall quality and constructability of building systems.